Implikatur dan Maksud Tuturan Berbahasa Jawa dalam Antologi Cerkak Simbar Menjangan Karya Impian Nopitasari - Sarwo Edi Wardana (Universitas Sebelas Maret, 2024)
People sometimes do not clearly state what they mean, but instead, use other statements that are certainly understood by their speaking partner. This is an implication. Implications can also be found in the form of Javanese language statements because of the characteristic of Javanese people who tend to be indirect in expressing something. This article aims to discuss the implications and the meanings of Javanese language statements in the anthology of cerkak (cerita cekak)/'short stories' entitled Simbar Menjangan (2022) by Impian Nopitasari. This object was chosen because the speech in it is pragmatically close to everyday life and contains various Javanese speeches against the backdrop of plural Javanese life stories, such as urban and rural life, migration, relations between two cultures, and so on. This article is a descriptive-qualitative study with data collection through the observe-record method and data processing and analysis using the contextual pragmatic matching method. The theory of implication is used to examine the principle of cooperation through four maxim principles developed by Grice (1989), that's quantity maxim, quality maxim, relation maxim, and manner maxim. The results of the study show that (1) there are seven meanings in implications, including allowing, convincing, providing reasons, agreeing (as politeness), inciting gossip, rejecting/avoiding gossip, and opening/inciting conversation; (2) the meanings of implications in the Javanese language statements have their characteristics, i.e. many statements are found that have different meanings or convey meanings or information that are not direct. This is certainly based on Javanese social and cultural aspects, such as habits, politeness, formality, and familiarity.